Exploring the Impact of Leadership Characteristics on Subordinates’ Counterproductive Work Behavior: From the Organizational Cultural Psychology Perspective - Shen, Yaoping; Lei, Xinghui (Frontiers in Psychology, 2022)
Counterproductive work behaviors (CWBs) are extremely detrimental to an organization and its stakeholders as they impact economic efficiency and damage the atmosphere within the organization. Leaders are in a position of authority, have resources and decision-making power, and their words and actions are noticed and imitated by employees. From a leadership perspective, an effective way to avoid CWBs is to seek ways to intervene in the occurrence and escalation of CWBs. First, after coding and analyzing the interview transcripts of employees in a company, we conducted a grounded theory study on the leadership characteristics which are antecedent variable of CWBs, and the leadership characteristics were divided into three categories: psychological, behavioral, and ability. These characteristics impact subordinates’ CWBs. Second, based on the conservation of resource theory, we conducted an ecological validation of the mechanism through which leadership characteristics affect subordinates’ CWBs, explored the impact of different leadership characteristics on subordinates' perception of resources, and further explored the mediation of work and personal resources. The results indicate that all three types of leadership characteristics have a negative predictive effect on subordinates’ CWBs and that the mediation of work resources holds while that of personal resources holds partly. An advantage analysis was conducted to depict the effects of the three types of leadership characteristics on subordinates’ CWBs. The results show that the three types of characteristics have a similar effect on CWBs based on interpersonal ties, while ability characteristics show a more significant effect on CWBs directed at organizations.